Contributions of the Project "Chamber Music Tour" for the Dissemination of Cultural Production, Public Education and Transdisciplinarity - Belém, Alice; Baêta Zille, José Antônio; Ramos, Fábio (Guará Journal, 2019)
This paper describes the actions of the project “Chamber Music Tour” under development at the Minas Gerais State University (UEMG) during the year 2018. The project consists in the production of concerts for students’ chamber music ensembles in the units of such university in Belo Horizonte. Its contributions are related not only to the students’ education, but also to the enhancement of academic artistic production. In addition, the project encourages interdisciplinarity and transdisciplinarity, as well as the exchange of cultural experiences among the university community. The project’s contributions extend to the current context of Brazilian society, poor of initiatives that expand access to some of the cultural assets of mankind